Benchmarking PET for geoscientific applications: 3D quantitative diffusion coefficient determination in clay rock. (April 2017) - Lippmann-Pipke, J.; Gerasch, R.; Schikora, J.; Kulenkampff, J.
Abstract: The 3D diagonal anisotropic effective diffusion coefficient of Na +, D eff =(D xx, D yy, D zz ), was quantified in a clay material in one single experiment/simulation. That is possible due to the combination of the non-invasive observation of Na + diffusion in Opalinus clay by means of GeoPET method (PET: positron emission tomography) followed by quantitative 3D+t data evaluation by means of the finite element numerical modelling (FEM). The extracted anisotropic effective diffusion coefficient parallel ( || ) and normal ( ⊥ ) to the bedding of the clay rock, D eff =(D ||, D ⊥, D || ) are comparable to those obtained on earlier experimental studies in the same clay material but with different methods. We consider this study as benchmark for the long-standing development of our GeoPET method, that explicitly includes a resolute and physics based attenuation and Compton scatter correction algorithm (Kulenkampff, J., M. Gründig, A. Zakhnini and J. Lippmann-Pipke (2016). "Geoscientific process monitoring with positron emission tomography (GeoPET)." Solid Earth 7: 1217–1231) . We suggest GeoPET based fluid flow transport visualization combined with computer based process simulation henceforth as a qualified way for the quantification of three-dimensional, effective transport parameters in geosciences. Highlights: Benchmark study of transport process monitoring by means of PET. Numerical model inversely fits D eff to 3D+t GeoPET data set. Obtained anisotropic Na + diffusion coefficient for clay are realistic. We suggest GeoPET as a most qualified way for flow process monitoring in geomaterials.